Varieties of envy. (18th May 2016) - Protasi, Sara
Abstract: In this paper I present a novel taxonomy of envy as a psychological state, according to which there are four kinds of envy: emulative, inert, aggressive, and spiteful envy. The first section introduces the intuition that there is more than one kind of envy, together with the anecdotal and linguistic evidence that supports it. The second section proposes and explains in detail a definition of envy tout court. The third section presents a recurring distinction between the behavioral tendencies of envy that have been explained in two distinct ways, one mostly proposed by psychologists, the other discernible in the philosophical tradition. The fourth section argues that these models of explanation track two variables—focus of concern and obtainability of the good—whose interplay is responsible for the existence of the four kinds of envy. The fifth section illustrates four paradigmatic cases and provides a detailed analysis of the phenomenology, motivational structure, and typical behavioral outputs of each. The paper ends with a brief discussion of the implications of the taxonomy for moral education.